1999
DOI: 10.1007/s004250050628
|View full text |Cite
|
Sign up to set email alerts
|

pH and buffer capacities of apoplastic and cytoplasmic cell compartments in leaves

Abstract: After opening the stomata in CO(2)-free air, darkened leaves of several plant species were titrated with CO(2) at concentrations between 1 and 16%, in air in order to reversibly decrease cellular pH values and to calculate buffer capacities from pH changes and bicarbonate accumulation using both gas-exchange and fluorescence methods for analysis. After equilibration with CO(2) for times ranging between 4.4 and 300 s, fast CO(2) release from bicarbonate indicated catalysis by highly active carbonic anhydrase. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 30 publications
1
32
0
Order By: Relevance
“…It represents a first signal of plant-fungal contact, mediates enzyme activities, and controls membrane transport of metabolizable compounds. This impact is possible because its buffer capacity of around 5 mM H + /pH unit (Hanstein and Felle, 1999;Oja et al, 1999) is relatively low (compared with the roughly 10 times higher buffer capacity of the cytoplasm). With respect to the raised question, to what extent the fungus can increase its access to the host's organic resources, it is concluded that the measured pH changes reflect defence responses of the host against the ARTICLE IN PRESS Figure 6.…”
Section: Resultsmentioning
confidence: 96%
“…It represents a first signal of plant-fungal contact, mediates enzyme activities, and controls membrane transport of metabolizable compounds. This impact is possible because its buffer capacity of around 5 mM H + /pH unit (Hanstein and Felle, 1999;Oja et al, 1999) is relatively low (compared with the roughly 10 times higher buffer capacity of the cytoplasm). With respect to the raised question, to what extent the fungus can increase its access to the host's organic resources, it is concluded that the measured pH changes reflect defence responses of the host against the ARTICLE IN PRESS Figure 6.…”
Section: Resultsmentioning
confidence: 96%
“…Apart from enhanced metabolite channeling, terpene synthases have a sharp pH optimum between 6 and 7 (Fischbach et al, 2000). Given that in actively photosynthesizing chloroplasts, the pH is around 8, while the cytosol is more acidic (Oja et al, 1999), heat and cold stress-dependent alterations in membrane permeability can create pH conditions in plastids more suitable for terpene synthesis. Rapid changes in terpene synthesis capacity and release have been observed in developing flowers (Nagegowda et al, 2008), and clearly more experimental work is needed to gain insight into rapid modifications in terpene release.…”
Section: Emissions Of Monoterpenes Under Stressmentioning
confidence: 98%
“…The cytosolic buffering capacity of plant cells has been reported to be some 10 orders of magnitude larger than the apoplastic buffer capacity. Depending on the cell type and organism, a change in proton concentration of between 25 mM and 90 mM is required to change cytosolic pH by one unit (Plieth et al , 1997; Plieth and Hansen, 1998; Schönknecht and Bethmann, 1998; Oja et al , 1999). In leaves, the apoplastic buffering capacity has been reported to be ∼4 mM pH −1 (Oja et al , 1999).…”
Section: Introductionmentioning
confidence: 99%